Understanding the impact and causes of 'failure to attend' on continuity of care for patients with chronic conditions - Byrne, A.L.; Baldwin, A.; Harvey, C.; Brown, Janie; Willis, E.; Hegney, D.; Ferguson, B.; Judd, J.; Kynaston, D.; Forrest, R.; Heritage, B.; Heard, D.; et al. (PUBLIC LIBRARY SCIENCE, 2021)
Aim: To understand the impact and causes of 'Failure to Attend' (FTA) labelling, of patients with chronic conditions.